Migration and hybridity or the outsiders of contemporary Greek literature - Recuenco-Peñalver, María (Universidad de Chile, 2024)
In a globalised world, the understanding of literature under a transnational approach brings to light aspects that profoundly challenge some traditional literary assumptions in terms of literary genres, writing roles and even personal belonging. Greece, as country of migrants, provides us with the case of contemporary multilingual literature that draws attention to some of these aspects, from the point of view of diaspora and migrant studies, as well as multilingualism and multiculturalism. This paper shall focus on the case of seven Modern Greek authors, to illustrate the importance of the experience of Greek diaspora in connection with literary creation and identity dilemmas. By doing so, it is our intention to underline the need for a rethinking of the practice of self-translation, and the relationship between xenitia, identity and belonging in the study of what we call Modern Greek migrant literature.
Migración e hibridez o los extranjeros de la literatura griega contemporánea
Keywords: Griego moderno; Modern Greek; Self-translation; Autotraducción; Literature; Literatura; Hybridity; Hibridez; Migración; Migration; Xenitia